The Relation of Psychosocial Distress With Myocardial Perfusion and Stress-Induced Myocardial Ischemia. Issue 4 (May 2019) - Pimple, Pratik; Hammadah, Muhammad; Wilmot, Kobina; Ramadan, Ronnie; Al Mheid, Ibhar; Levantsevych, Oleksiy; Sullivan, Samaah; Lima, Bruno B.; Kim, Jeong Hwan; Garcia, Ernest V.; Nye, Jonathon; Shah, Amit J.; et al.
ABSTRACT: Objective: Mental stress–induced myocardial ischemia is a frequent phenomenon in patients with coronary artery disease (CAD). The link between an integrated measure of chronic psychosocial distress and mental stress–induced myocardial ischemia, and whether it differs by sex, has not been examined before. Methods: We used latent class analysis to derive a composite measure of psychosocial distress integrating scales of depression, posttraumatic stress, anxiety, anger, hostility, and perceived stress in 665 individuals with stable CAD. Participants underwent myocardial perfusion imaging with mental stress and perfusion defects were quantified at rest (summed rest score), with mental stress (summed stress score), and their difference (summed difference score), the latter being an index of inducible ischemia. Results: The M (SD) age was 63 (9) years, and 185 (28%) were women. Latent class analysis characterized the study sample into four distinct classes of incremental psychosocial distress. In women, class 4 (highest distress) had an adjusted 4.0-point higher summed rest score (95% confidence interval = 0.2–7.7) as compared with class 1 (lowest distress), whereas no difference was observed in men (−0.87 points, 95% confidence interval = −3.74 to 1.99, p = .04 for interaction). There was no association between the psychosocial distress latent variable and summed difference score in either women or men. Conclusions: Among patients with CAD, a higher level of psychosocial distress is not associated with mental stress ischemia, but it is associated with more resting (fixed) perfusion abnormalities in women only, as well as with blunted hemodynamic response to mental stress in both men and women. Abstract : Supplemental digital content is available in the text.